'Swinging the lead and working the head' – An explanation as to why mental illness stigma is prevalent in policing. (March 2022) - Bell, Sean; Palmer-Conn, Sue; Kealey, Nick
Policing can be injurious to the mental health of those delivering the service. The causes can be operational, organisational or a mixture of both. Mental health related stigma is prevalent within policing; thus, help seeking is avoided. Those who do seek help are often thought to be malingerers. Managers are considered to be ill equipped to identify and support those at risk. The processes and policies that are meant to support recovery do not meet the needs of the officers and staff living and working with mental ill health. Consequently, disclosing a mental health issue is seen as career destroying.